2017
DOI: 10.1111/jth.13484
|View full text |Cite
|
Sign up to set email alerts
|

Management of direct oral anticoagulants in women of childbearing potential: guidance from the SSC of the ISTH: comment

Abstract: We welcome the recent guidelines from the SSC of the ISTH, which provide much-needed guidance on the management of direct oral anticoagulants (DOACs) in women of childbearing potential [1]. We agree with the guidance except for one area, and feel there would be benefit in reconsidering one of the recommendations: 'Should pregnancy be desired, we recommend that the DOAC is switched to an alternative anticoagulant preconceptually, with the main alternative anticoagulant options vitamin K antagonists (VKAs) (to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…53 The International Society on Thrombosis and Hemostasis (ISTH) recommends against the use of DOACs during pregnancy and also advises on the use of anticoagulants other than DOACs in women trying to become pregnant. 54 Systemic thrombolysis must be considered in pregnant patients with life-threatening hemodynamic instability due to massive PE. A recent literature review summarized 23 case reports on the use of systematic thrombolysis as treatment for massive PE in pregnant patients.…”
Section: Treatment Of Acute Pulmonary Embolism In Pregnancymentioning
confidence: 99%
“…53 The International Society on Thrombosis and Hemostasis (ISTH) recommends against the use of DOACs during pregnancy and also advises on the use of anticoagulants other than DOACs in women trying to become pregnant. 54 Systemic thrombolysis must be considered in pregnant patients with life-threatening hemodynamic instability due to massive PE. A recent literature review summarized 23 case reports on the use of systematic thrombolysis as treatment for massive PE in pregnant patients.…”
Section: Treatment Of Acute Pulmonary Embolism In Pregnancymentioning
confidence: 99%
“…The decision to prefer VKA to LMWH is influenced by the uncertain time to conception and the side effects of long‐term use of LMWH. Some clinicians and patients prefer to switch directly from DOAC to LMWH after a positive pregnancy test, although data on safety of DOAC in very early pregnancy are extremely scarce . In those cases, we recommend reporting the DOAC exposure in early pregnancies to the International Society of Thrombosis and Haemostasis registry…”
Section: Pregnancymentioning
confidence: 99%
“…We feel that this constitutes a reasonable and objective approach to acquire the relevant information on DOACs that would, in turn, underpin a revised recommendation in due course, based on emerging evidence. [1]. The authors showed that elevated mean platelet volume (MPV) at admission was associated with poor neurological outcomes and mortality at 30 days.…”
Section: H C O H E N * † D R a R A C H C H I L L A G E * S mentioning
confidence: 99%
“…Management of direct oral anticoagulants in women of childbearing potential: guidance from the SSC of the ISTH: reply We thank Desborough et al for their response to the recently published guidance from the SSC of the ISTH on the management of direct oral anticoagulants (DOACs) in women of childbearing potential [1,2]. We have carefully examined their view and seriously considered their proposal regarding the recommendation of this guidance as detailed below.…”
mentioning
confidence: 99%
See 1 more Smart Citation